PENGARUH EXPERIENTIAL MARKETING DAN PRODUK VALUE TERHADAP KEPUASAN WISATAWAN DI KAWASAN WISATA KERINCI DAN SUNGAI PENUH - Halil Khusairi; Wawan Novianto (Juremi: Jurnal Riset Ekonomi, 2025)
This article discusses Kerinci as a representation of culture and nature in Sumatra, with a focus on Mount Kerinci and its surroundings. The article also describes challenges in the tourism industry, including competition and the importance of building long-term relationships with customers. The article attempts to analyze the factors influencing consumer decisions in choosing tourism products and the significance of customer experience in the hospitality and tourism industry, with an explanation of the concept of experiential marketing. The article also analyzes the importance of customer satisfaction in building loyalty and the value they receive from service providers. The data analysis method used in this research is partial least squares (PLS), which was developed as an alternative modeling with a weak foundational theory compared to structural equation modeling (SEM). As a result, the development of Sharia tourism in Kerinci Regency, Jambi Province, needs to focus on customer satisfaction, service quality, prices that comply with Sharia principles, and tourism experiences that incorporate religious elements. Therefore, this destination can attract visitors, build customer loyalty, and meet the expectations of those seeking tourism experiences in line with Sharia values.